Effect of micrografting technique on growth and cold resistance of tea (Camellia sinensis) plant - Cheng, Yaohua; Lin, Mengling; Wang, Hongying; Zhou, Ziwen; Long, Linxin; Yang, Qi; Ban, Qiuyan; Zhang, Xianchen; Li, Yeyun (BMC plant biology, 2025)
Micrografting technology has gained popularity in model plants, with the advantages of a wide grafting range and small space. However, this technique has not been fully explored in tea plants. In our study, different rootstocks [radicle (obtained from the germination in seed), epicotyl without cotyledons, epicotyl with cotyledons, tea varieties] and scion (red branch, green branch) grafting combinations were used to estimate the survival rate, plant growth, the compatibility behavior, and cold tolerance of grafted seedlings. Our results showed that the higher survival rate and shooting rate were observed in radicle (obtained from the germinated seed diameter ≥ 15 mm, D3) as the rootstock. Also, the same growth indicators were found in the green branch as scion and radicle as rootstock (GB\R) were higher than that of other grafting combinations. In addition, the grafted seedlings of LJ43 as rootstock had the best growth rate, and the vascular bundle bridge was completely established in SCZ as scion and LJ43 as rootstock (SCZ/LJ43) graft combination, accompanied with a higher survival rate, shoot rate and leaf number of new shoots and cold tolerance in field experiments. Our findings provide a viable tea micrografting method, which has the potential to substitute traditional tea cuttings for tea seedling propagation and thus meet the requirements of tea cultivation.